Associations between the Classroom Learning Environment and Student Engagement in Learning 1: A Rasch Model Approach - Cavanagh, Robert (Australian Association for Research in Education (AARE), 2012)
This report is about one of two phases in an investigation into associations between student engagement in classroom learning and the classroom learning environment. Both phases applied the same instrumentation to the same sample. The difference between the phases was in the measurement approach applied. This report is about application of the Rasch model to analyse the data; the second report (Associations between the Classroom Learning Environment and Student Engagement in Learning 2: A Structural Equation Modeling Approach), is about Structural Equation Modeling application. Student engagement in learning has become an important consideration in research into learning environments and the design of instruction. This study applied a novel model of engagement in classroom learning based on flow theory and bio-ecological frameworks. The objectives were to construct a composite measure of student engagement in classroom learning and the classroom learning environment. Then, to compare student scores for variables and groups of students (e.g. boys and girls). An 85-item scale was created and data from administering the scale to 1760 secondary school students were tested for fit to the Rasch rating scale measurement model. Data on engagement in classroom learning and the classroom learning environment were able to be plotted on one interval scale suggesting an underlying common construct. Also, there were statistically significant differences in overall student scores between country and city students, boys and girls, year cohorts, curriculum areas, and favourite and non-favourite subjects.